2018
DOI: 10.1080/2162402x.2018.1484981
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic treatment of multiple myeloma mediates tumor intrinsic and extrinsic immunomodulatory effects

Abstract: Immune evasion is an important driver of disease progression in the plasma cell malignancy multiple myeloma. Recent work highlights the potential of epigenetic modulating agents as tool to enhance anti-tumor immunity. The immune modulating effects of the combination of a DNA methyltransferase inhibitor and a histone deacetylase inhibitor in multiple myeloma is insufficiently characterized. Therefore, we used the murine immunocompetent 5T33MM model to investigate hallmarks of immunogenic cell death as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…12,24,57,113,119,224,237 Ultimately, APCs engulfing TAAs or TSAs and receiving these immunostimulatory cues acquire an extraordinary ability to crosspresent TAA-or TSA-derived epitopes to CD4 + and/or CD8 + T cells in the context of co-stimulation, which enables TAA/TSAtargeting immunity. [239][240][241][242][243][244] In multiple oncological settings, cancer cells capable of undergoing ICD in response to microenvironmental or therapeutic stress are subjected to increased immunological pressure, 245 resulting in the selection of poorly immunogenic tumor variants displaying: (1) reduced antigenicity (due to TAA/TSA loss or defects in MHC Class I exposure); [246][247][248][249][250][251][252][253] (2) genetic or epigenetic annihilation of the intracellular stress pathways that support the emission of ICD-associated DAMPs, cytokines or chemokines; 254 and/or (3) direct genetic or epigenetic silencing of specific DAMPs (e.g. CALR) or type I IFN.…”
Section: Introductionmentioning
confidence: 99%
“…12,24,57,113,119,224,237 Ultimately, APCs engulfing TAAs or TSAs and receiving these immunostimulatory cues acquire an extraordinary ability to crosspresent TAA-or TSA-derived epitopes to CD4 + and/or CD8 + T cells in the context of co-stimulation, which enables TAA/TSAtargeting immunity. [239][240][241][242][243][244] In multiple oncological settings, cancer cells capable of undergoing ICD in response to microenvironmental or therapeutic stress are subjected to increased immunological pressure, 245 resulting in the selection of poorly immunogenic tumor variants displaying: (1) reduced antigenicity (due to TAA/TSA loss or defects in MHC Class I exposure); [246][247][248][249][250][251][252][253] (2) genetic or epigenetic annihilation of the intracellular stress pathways that support the emission of ICD-associated DAMPs, cytokines or chemokines; 254 and/or (3) direct genetic or epigenetic silencing of specific DAMPs (e.g. CALR) or type I IFN.…”
Section: Introductionmentioning
confidence: 99%
“…In case bona fide ICD occurs, mice will be protected against a challenge with living tumor cells. We were the first to perform this vaccination assay using the syngeneic immunocompetent 5T33MM model (De Beck et al, 2018). The vaccine consisted of 5T33vt cells treated with bortezomib, melphalan, a DNA methyltransferase inhibitor (decitabine), a histone deacetylase inhibitor (quisinostat) or the combination of decitabine and quisinostat.…”
mentioning
confidence: 99%
“…However, use of AZA or decitabine in MM is limited because of induction of DNA damage. Recent research showed that decitabine enhanced the effect of bortezomib in an MM cell line (29). Decitabine, combined with quisinostat, a histone deacetylase inhibitor, showed increased antimyeloma effects and altered immune cell constitution, such as increased dendritic cells and naive T cells, in a mouse myeloma model (30).…”
Section: Discussionmentioning
confidence: 99%